Three-dimensional photoacoustic imaging by sparse-array detection and iterative image reconstruction - Ephrat, Pinhas; Keenliside, Lynn; Seabrook, Adam; Prato, Frank S; Carson, Jeffrey J L (Journal of biomedical optics, 2008)
Photoacoustic imaging (PAI) has the potential to acquire 3-D optical images at high speed. Attempts at 3-D photoacoustic imaging have used a dense 2-D array of ultrasound detectors or have densely scanned a single detector on a 2-D surface. The former approach is costly and complicated to realize, while the latter is inherently slow. We present a different approach based on a sparse 2-D array of detector elements and an iterative reconstruction algorithm. This approach has the potential for fast image acquisition, since no mechanical scanning is required, and for simple and compact construction due to the smaller number of detector elements. We obtained spatial sensitivity maps of the sparse array and used them to optimize the image reconstruction algorithm. We then validated the method on phantoms containing 3-D distributions of optically absorbing point sources. Reconstruction of the point sources from the time-domain signals resulted in images with good contrast and accurate localization (< or =1 mm error). Image acquisition time was 1 s. The results suggest that 3-D PAI with a sparse array of detector elements is a viable approach. Furthermore, the rapid acquisition speed indicates the possibility of high frame rate 3-D PAI.